2016
DOI: 10.1002/cre2.39
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontal condition and kidney dysfunction in Japanese adults: A cross‐sectional study

Abstract: Recent studies have demonstrated that chronic kidney disease (CKD) may be associated with the progression of periodontal disease. Diabetes mellitus (DM) is a major risk factor for CKD. The objective of this study was to clarify the relationship between periodontal condition and kidney dysfunction in patients who had kidney failure with or without DM. One hundred sixty‐four patients with kidney dysfunction were enrolled (male: N = 105; female: N = 59), and the relationship between periodontal condition and kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
17
2
Order By: Relevance
“…Our study showed that diabetic patients with renal dysfunction had fewer remaining teeth and less likelihood to have 20 or more remaining teeth, as compared with those with normal renal function. Previous evidence consistently revealed a significant correlation between deceased kidney function and the number of missing teeth attributing to periodontal disease in patients with or without diabetes [28]. A smaller number of teeth also results in reduced inflammation from the periodontal area.…”
Section: Discussionmentioning
confidence: 89%
“…Our study showed that diabetic patients with renal dysfunction had fewer remaining teeth and less likelihood to have 20 or more remaining teeth, as compared with those with normal renal function. Previous evidence consistently revealed a significant correlation between deceased kidney function and the number of missing teeth attributing to periodontal disease in patients with or without diabetes [28]. A smaller number of teeth also results in reduced inflammation from the periodontal area.…”
Section: Discussionmentioning
confidence: 89%
“…Naruishi et al showed higher rate of periodontal problems in patients with diabetic nephropathy and negative correlation between glomerular filtration rate and the number of missing teeth in Japanese adults (26). Missing teeth were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Some studies compared diabetic versus nondiabetec ESRD patients. However, there were no significant differences between diabetic and nondiabetic ESRD patients regarding several periodontal parameters (Chuang et al, 2005;Murali et al, 2012;Naruishi et al, 2016;Swapna et al, 2013).…”
Section: Discussionmentioning
confidence: 99%